Pengembangan Model Pencegahan Anak-Anak Terminal dari Kekerasan Sosial dengan Pendekatan Berbasis Kekuatan dan Kewirausahaan Sosial - Wibowo, Hery (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2012)
Social violence is an issue that is always present throughout the life of human civilization. Social violence comes very close to human life in various domains of life. One thing to note from social violence is its potential to make children (and other young people) are victims and perpetrators of violence themselves socially. Social Welfare, actually has several approaches, perspectives and instruments to interact with issues of social violence. However, it is less often discussed in the scientiﬁ c writing. This paper attempts to model the handling of violence through social welfare income and social entrepreneurship. Keywords: kekerasan sosial, pendekatan kesejahteraan, social entrepreneurship.